2017
DOI: 10.1016/j.gheart.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Overlaps Between the Genomic and Environmental Determinants of LVH and Stroke: A Multicenter Study in West Africa

Abstract: Background Whether left ventricular hypertrophy (LVH) is determined by similar genomic and environmental risk factors with stroke, or is simply an intermediate stroke marker, is unknown. We present a research plan and preliminary findings to explore the overlap in the genomic and environmental determinants of LVH and stroke among Africans participating in the Stroke Investigative Research and Education Network (SIREN) study. Methods SIREN is a transnational, multi-centre study involving acute stroke patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
5
1
Order By: Relevance
“…This study aimed to investigate the burden and early outcomes of LVH among young adults with rst ever stroke admitted at a tertiary hospital in Tanzania. We found that three-quarters of young stroke participants had LVH as diagnosed by TTE, which is higher than that described in a West African study by Adeoye et al, were 55% of the blacks (mean age of 59.1±13.2 years) with rst stroke had LVH (12). The authors also found that younger age ≤45 years was independently associated with LVH, suggesting an underlying genetic factor in the pathogenesis which merits further investigation.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…This study aimed to investigate the burden and early outcomes of LVH among young adults with rst ever stroke admitted at a tertiary hospital in Tanzania. We found that three-quarters of young stroke participants had LVH as diagnosed by TTE, which is higher than that described in a West African study by Adeoye et al, were 55% of the blacks (mean age of 59.1±13.2 years) with rst stroke had LVH (12). The authors also found that younger age ≤45 years was independently associated with LVH, suggesting an underlying genetic factor in the pathogenesis which merits further investigation.…”
Section: Discussioncontrasting
confidence: 60%
“…Independent predictors for LVH were: younger age (<45 years), female gender and uncontrolled hypertension (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to whites, Africans with or without stroke are more likely to have LVH across all age groups. Adeoye et al in West Africa found that in a cohort of stroke participants above 18 years, younger age (≤ 45 years), female gender and uncontrolled hypertension was independently associated with LVH [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In SSA, there is a high burden of LVH (up to 50%) particularly among untreated hypertensive patients [ 10 ]. A study in West Africa revealed that more than half of the stroke patients were found to have LVH by electrocardiogram: independent predictors for LVH included younger age (< 45 years), female gender and uncontrolled hypertension [ 11 ]. Transthoracic echocardiography (TTE) is a noninvasive modality of choice to assess cardiac structure and function (including the detection of LVH) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%